The self-assessment accuracy and its relationship with performance and individual characteristics - Roh, YounHee; Sohn, YoungWoo (Korean Journal of Industrial and Organizational Psychology, 2011)
This study investigated the effects of self-assessment accuracy on individual performance. The self-assessment accuracy was defined as the degree of agreement between self- and other-assessments. A total of 158 subjects assessed themselves and others in their groups on the extent to which they actively participate in their group-based task. Following the method of Atwater and Yammarino (1997), subjects were classified into four groups. Individuals assessed as high by self and others, low by self and others, high by self and low by others, and low by self and high by others were categorized as in-agreement/high assessors, in-agreement/low assessors, over-estimators, and under-estimators, respectively. To test the hypothesis that in-agreement/high assessors will show greater performance than in-agreement/low assessors, over-estimators, and under-estimators, one-way ANOVAs and post-hoc analysies were used. The results showed that in-agreement/high assessors showed greater performance (i.e., final record) than in-agreement/low assessors and over-estimators, and so the hypothesis was partially supported. In addition, this study tested the hypotheses that in-agreement/high assessors will show better indices in such individual characteristics as internal locus of control, self-esteem, self-efficacy, conscientiousness, and neuroticism than in-agreement/low assessors, over-estimators, and under-estimators. The results showed that in-agreement/high assessors showed higher self-efficacy and conscientiousness than in-agreement/low assessors, and so the hypotheses were partially supported.